2022
DOI: 10.31557/apjcp.2022.23.12.4145
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Effects on Cell Cycle Arrest and Apoptosis and Doxorubicin Activity in T47D Cancer Stem Cells

Abstract: Backgrounds: Targeting breast cancer stem cells with the CD44+/CD24-phenotype is critical for complete eradication of cancer cells due to its Self-renewal, differentiation, and therapeutic resistance ability. Quercetin is a popular flavonoid with lower adverse effects and has anti-tumor properties. Therefore, we assessed the anticancer activity of Quercetin and Doxorubicin alone and in combination in the T47D cells of human breast cancer and their isolated Cancer stem cells (CSCs). Materials and Methods: The h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…QUE can also support conventional treatment methods. Studies performed using breast cancer cells showed that the addition of QUE to doxorubicin enhanced the induction of apoptosis in T47D cells [ 76 ]. In Figure 2 , the impact of flavonols on the regulation of apoptosis pathways is depicted.…”
Section: Apoptosismentioning
confidence: 99%
“…QUE can also support conventional treatment methods. Studies performed using breast cancer cells showed that the addition of QUE to doxorubicin enhanced the induction of apoptosis in T47D cells [ 76 ]. In Figure 2 , the impact of flavonols on the regulation of apoptosis pathways is depicted.…”
Section: Apoptosismentioning
confidence: 99%
“…Dox, PTX, VCR, and QUE combined treatment substantially reduces ABCB1/P-gp expression and eliminates breast CSCs ( Li S. et al, 2018 ). Additionally, quercetin suppresses colorectal and breast CSCs ( Azizi et al, 2022 ). QUE can control HIF-1α, which re-sensitizes 4T1 cells, MCF-7/Dox cells, and HCT116 cancer cells to DDP and etoposide ( Kim et al, 2012 ).…”
Section: Natural Product—derived Compounds Overcome Cancer Drug Resis...mentioning
confidence: 99%
“…The antitumor aspect involves breast cancer, liver cancer, colon cancer, etc. [ 65 , 66 , 67 , 68 , 69 , 70 ]. However, there are application limitations related to the stability of use in vivo, which limits the use of quercetin [ 71 ].…”
Section: Polyphenolic Compoundsmentioning
confidence: 99%